MANAGEMEN PENGEMBANGAN BUDAYA MEMBACA UNTUK ANAK USIA DINI MELALUI POP UP BOOKS - Yunindyah Wulan; Rahmat Mulyono (STKIP Subang, 2023)
Reading culture is a behavior that grows from a process of repeated habituation. Building a reading culture for early childhood starts from things that are close to children, concrete and interesting. Early childhood is a child who is in a period of growth and development. The period in which the child will quickly absorb the various stimuli given to him. Building a reading culture is not an easy matter, therefore it needs to be built from an early age. Pop up books are an alternative book that can be used as a teacher to foster children's interest in reading. By growing interest in reading, then through habituation, it is hoped that a reading culture can be awakened. The method used is the method of literature study. The literature study carried out by researchers is to search for various written sources, both in the form of books, articles, and relevant journals. The results showed 1) Planning for the development of a reading culture was carried out by compiling a cultural program team reading, making reading programs, procuring facilities and books reading media based on pop up books, 2) Implementation is carried out by socializing reading programs, creating pop up media based images, reading corner programs, literacy days and having mobile libraries, 3) Evaluation is carried out by monitoring field activities and follow-up.